The effects of wood anisotropy on the mode of attack by the woodborer Teredo navalis and the implications for underwater cultural heritage. (February 2016) - Eriksen, Anne Marie; Gregory, David John; Villa, Chiara; Lynnerup, Niels; Botfeldt, Knud Bo; Rasmussen, Arne Redsted
Abstract: Marine borers such as the shipworm, Teredo navalis, can cause great destruction to wooden archaeological remains in the marine environment. The focus of this study was to investigate whether shipworm preferentially settle on one orientation of the wood over another, i.e. radial, tangential or transversal and if the resulting tunnels are oriented in a specific direction according to the fibres within the wood. This was investigated using Computed Tomography (CT) scanning and subsequent 3D modelling as a method of both quantifying the severity of attack by shipworm and examining the orientation of the tunnels. Panels of pine, cut in tangential, radial and transversal planes, were placed in the sea at a location where shipworm was known to be abundant. After attack, the panels were weighed, X-rayed, entrance holes counted and 3D CT models created. All results show a difference between the three planes. The specific direction of the single tunnels could be evaluated using the CT models, since the individual tunnels could be isolated, and followed throughout the panel. The results show that the radial plane suffered a more severe attack than either of the two other planes. These results have implications for archaeological interpretation and conservation. For example, the results show that ancient ships built with timbers cut in a radial plane (e.g. Viking Ships or other structural elements cut in radial plane) may be more prone to attack and thus require more protection than those built in tangential or transversal plane should they be raised (difficulties lifting due to fragility) or preserved in situ . Highlights: CT scanning was used to quantifying the severity of attack by shipworm and for examination of the orientation of the tunnels. The mode of attack varies in the three wooden planes (tangential, radial and longitudinal), with preferential attack in the radial plane. The attack is likely to follow the grain of the wood once the shipworm larvae have settled and start boring.